Respuesta :

Answer:

see explanation

Step-by-step explanation:

the equation of a parabola in vertex form is

y = a(x - h)² + k

where (h, k) are the coordinates of the vertex and a is a multiplier

(1)

(h, k) = (1, - 4)

y = a(x - 1)² - 4

to find a use any other point that lies on the graph and substitute the coordinates into the equation

using (0, - 3), then

- 3 = a(- 1)² - 4

- 3 = a - 4 ⇒ a = - 3 + 4 = 1

y = (x - 1)² - 4 ← equation in vertex form

(2)

(h, k) = (1, - 10)

y = a(x - 1)² - 10 → using (3, - 2)

- 2 = 4a - 10 ⇒ 4a = 8 ⇒ a = 2

y = 2(x - 1)² - 10 ← equation in vertex form

(3)

(h, k) = (2, 1)

y = a(x - 2)² + 1 → using (3, 0)

0 = a + 1 ⇒ a = - 1

y = -(x - 2)² + 1 ← equation in vertex form